Atherogenesis, Inflammation and Autoimmunity - An Overview - Lakota, Katja; Artenjak, Andrej; Cucnik, Sasa; Brguljan-Hitij, Jana; Cegovnik, Borut; Salobir, Barbara; Accetto, Rok; Bozic, Borut; Rozman, Blaz; Sodin-Semrl, Snezna (IntechOpen, 2012)
None